LC-MS/MS Method for Serum Creatinine: Comparison with Enzymatic Method and Jaffe Method - Ou, Meixian; Song, Yunxiao; Li, Shuijun; Liu, Gangyi; Jia, Jingying; Zhang, Menqi; Zhang, Haichen; Yu, Chen (PLOS ONE, 2015)
Accurate quantification of creatinine (Cre) is important to estimate glomerular filtration rate (GFR). Differences among various methods of Cre quantification were previously noted. This study aims to develop a liquid chromatography tandem mass spectrometry (LC-MS/MS) method for serum Cre and compare this method with clinical routine methods. LC-MS/MS analysis was performed on API 4000 triple quadrupole mass spectrometer coupled with an Agilent 1200 liquid chromatography system. After adding isotope-labeled Cre-d3 as internal standard, serum samples were prepared via a one-step protein precipitation with methanol. The LC-MS/MS method was compared with frequently used enzymatic method and Jaffe method. This developed method, with a total run time of 3 min, had a lower limit of quantification of 4.4 μmol/L, a total imprecision of 1.15%–3.84%, and an average bias of 1.06%. No significant matrix effect, carryover, and interference were observed for the LC-MS/MS method. The reference intervals of serum Cre measured by LC-MS/MS assay were 41–79 μmol/L for adult women, and 46–101 μmol/L for adult men. Using LC-MS/MS as a reference, the enzymatic method showed an average bias of -2.1% and the Jaffe method showed a substantial average bias of 11.7%. Compared with the LC-MS/MS method, significant negative bias was observed for the enzymatic and Jaffe methods in hemolytic and lipimic samples. We developed a simple, specific, and accurate LC-MS/MS method to analyze serum Cre. Discordance existed among different methods.